Pengaruh Harga Produk dan Kualitas Produk Terhadap Keputusan Pembelian Mobil Pada PT.Sejahtera Buana Trada Surabaya - Wasklito Adi, Titok; Febrinanto Prakasa, Davis; Arifin, Syamsul (Economics and Sustainable Development, 2024)
The purpose of this study was to test and ascertain how price and product quality affect consumer choice in purchasing a car at PT Sejahtera Buana Trada Surabaya. The study population consisted of car buyers from PT Sejahtera Buana Trada Surabaya, and 125 people were sampled. The results of distributing questionnaires are the source of data. In data analysis, multiple linear regression is the method used. Less than 0.05, the t test findings show a significant value of 0.001, supporting the theory that product prices influence consumer decisions to buy. Customers will make more purchases when the price of goods is more reasonable. The t test results show that product quality has an effect on consumer purchasing decisions; the significance value is 0.000 less than 0.05. The ability of a product to influence consumer decisions to buy increases as product quality improves. R Square, the multiple coefficient of determination, is 0.527 (52.7%), in accordance with the findings of the coefficient of determination (R2) test. This shows that while other factors (including price and quality) influence 47.3% of the total, 52.7% of the two factors that influence purchasing decisions (Y) are product quality (X2) and price (X1